(untitled) (Bangladesh Critical Care Journal, 2023)
Background: Regional anaesthesia has become an important anaesthetic technique now a days. The use of spinal (subarachnoid) anaesthesia is often limited by the unwillingness of patients to remain awake during surgery. Pharmacologically induced tranquility improves acceptance of regional technique. Objective: This study compares Ketofol (Ketamine + Propofol) and Dexmedetomidine in terms of onset and recovery of sedation, haemodynamic effects, respiratory effects and adverse effects of both the drugs during elective Caesarian section under spinal anaesthesia. Materials and Methods: This randomized clinical trial included 60 ASA (American Society of Anaesthesiologists) grade I and II patients between age 20-40 years undergoing elective Caesarean sections under Subarachnoid anaesthesia during the period January 2022 to June 2022. Patients were randomly allocatedto one of two groups: Ketofol group (Group KP, n=30), who received Ketofol in a single dose of 0.5mg/kg (Ketamine-0.5mg/ kg+Propofol -0.5mg/kg) and Dexmedetomidine group (Group D, n=30), who received Dexmedetomidine in a single dose of 2mcg/kg. Spinal anaesthesiawas conducted by injecting a hyperbaric solution of 0.5% bupivacaine 3ml through a 25G spinal needle at L3-4 level. All parameters were documented at 5 min intervals until arousal of the patient. The onset of sedation i.e. time from iv (intravenous) injection of Ketofol or Dexmedetomidine to closure of eye lids (OAA/S score of 3) and the arousal time from sedation i.e. time from closing of the eye lids to OAA/S score of 5 ( patient is awake clinically) were noted. Any complication during operation was documented. Patient’s satisfaction with the sedation was assessed by the 5 point ‘Likert verbal rating scale’. Results: There was no significant difference of mean blood pressure and mean heart rate between the two groups in different time intervals (P>0.05). Time of onset of sedation was significantly delayed in Dexmedetomidine group (P<0.001). The arousal time i.e. duration of sedation was comparable between the two groups (P>0.05). Ketofol was associated with significantly higher incidence of some adverse effects like pain in arm during drug administration than Dexmedetomidine (33.33% vs 10%, P<0.05). Satisfaction with sedation was comparable between the two groups (66.66% vs 86.66%, P value 0.136). Conclusion: As duration of sedation was comparable between the two drugs but adverse effects was less with Dexmedetomidine, it is recommended that Dexmedetomidine is a better choice than Ketofol for sedation in single dose technique during Subarachnoid block for Caesarean section. Bangladesh Crit Care J March 2023; 11 (1): 13-18